The Bishops’ House in the Romanian Pastoral Village of Rășinari (Mărginimea Sibiului) and its Hidden Treasures: A Short Legal History of the Book of Village Boundaries and the Deed of Donation (1488, 1383) and Transmissionales in causa Possessionis Resinar contra Liberam Regiamque Civitatem Cibiniensem (1784) - Cosma, Ela (Eikón / Imago, 2023)
The study aims to present legal aspects of the medieval and premodern history of Rășinari, the greatest pastoral village in Mărginimea Sibiului (lying at the foot of the Southern Carpathians), whose inhabitants (mărgineni) were considered the richest Romanian transhumant shepherds. Based on methods pertaining to Cyrillic and Latin palaeography, ecdotics, and legal history, we analyse precious documents discovered in the Church Museum of Rășinari, contained in the 18th century Orthodox Bishops’ House: 1. the extract of a deed of donation made in 1383 by Voivode Radu Negru to the Saint Paraschiva Church in Rășinari; 2. the Book of village boundaries of 1488, describing a perambulation for the separation of boundaries between the Romanian village and the Saxon one of Cisnădie; 3. the manuscript volume Transmissionales in causa Possessionis Resinar contra Liberam Regiamque Civitatem Cibiniensem 1784 (1,318 pages), a veritable legal mirror reflecting juridical relations, procedures and lawsuits specific to South Transylvania under Habsburg suzerainty. The examination of the medieval Cyrillic-Romanian documents’ variants, late copies and even 18th century Latin translations highlights the conclusion regarding the special historical, linguistic and legal value of the treasures hidden in the Bishops’ House of Rășinari.